2019
DOI: 10.1039/c9sc02313e
|View full text |Cite
|
Sign up to set email alerts
|

Threading carbon nanotubes through a self-assembled nanotube

Abstract: Achieving the co-assembly of more than one component represents an important challenge in the drive to create functional self-assembled nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…According to Figure 11 b,c, the follows changes are remarked in the Raman spectra of the two constituents of the P3HT/M + S-SWNTs and P3HT/S-SWNTs composites: (i) an up-shift of the Raman line assigned to RBM from 164 cm −1 (black curve in Figure 11 b) and 168 cm −1 (black curve in Figure 11 c) to 168 cm −1 (red curve in Figure 11 b) and 171 cm −1 (red curve in Figure 11 c); (ii) the appearance of the Raman line of P3HT at 1379–1377 cm −1 and 1445 cm −1 ; and (iii) a decrease in the intensity of the Raman lines localized in the higher frequencies spectral range 2500–3500 cm −1 . Often, the up-shift of the RBM band was invoked as an evidence for the wrapping of the SWNTs surface with the macromolecular compounds [ 34 ] or water molecules [ 35 ], when π-π* or hydrogen bonds were established between these constituents.…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure 11 b,c, the follows changes are remarked in the Raman spectra of the two constituents of the P3HT/M + S-SWNTs and P3HT/S-SWNTs composites: (i) an up-shift of the Raman line assigned to RBM from 164 cm −1 (black curve in Figure 11 b) and 168 cm −1 (black curve in Figure 11 c) to 168 cm −1 (red curve in Figure 11 b) and 171 cm −1 (red curve in Figure 11 c); (ii) the appearance of the Raman line of P3HT at 1379–1377 cm −1 and 1445 cm −1 ; and (iii) a decrease in the intensity of the Raman lines localized in the higher frequencies spectral range 2500–3500 cm −1 . Often, the up-shift of the RBM band was invoked as an evidence for the wrapping of the SWNTs surface with the macromolecular compounds [ 34 ] or water molecules [ 35 ], when π-π* or hydrogen bonds were established between these constituents.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously observed that coaxial polymer-nanotube composites could be createdb ye lectrostatically binding fluorescent polyelectrolytes to the surfaceo fs elf-assembled NDI nanotubes. [10,12] The polymere mission in these composites was efficientlyq uenched throughe lectron/energy transfer between the polymer and the NDI nanotubes. The PDA coating on the NDI-KK nanofibers maintainsas urface z-potential that could be modulated by pH.…”
Section: Resultsmentioning
confidence: 99%
“…[11] However,t he polyelectrolyte coatings could be displacedb ye nvironmental factors, such as pH, ionic strength, and solvent, thereby limiting the generality of this method. [12] We reasoned that coating nanostructures with polydopamine (PDA)w ould produce robustc omposites more capableo fs ustainingc hanges of solvent, pH, or ionic strength. Polydopamine coatings on substrates are produced by the in situ, oxidative polymerization of dopamine (DA) in weaka lkaline solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). 158 The preformed NDI-bola nanotubes were segmented by sonication prior to mixing with SWNTs to reduce potential steric congestion upon entrapping carbon nanotubes. The resulting nanotube segments encapsulated SWNTs via electrostatic and cation-π interactions, meanwhile, the inherent thermodynamic propensity of supramolecular structures on self-healing [159][160][161] re-combined nanotube segments along the length of SWNTs to form the continuous coaxial coating (Fig.…”
Section: Entrapping Carbon Nanotubes With Amphiphilic Peptide Derivativesmentioning
confidence: 99%